Prevalence of prescription and effectiveness of analgesia for treating vaginal delivery pain - Juan Ignacio Calcagno; Sarah Iribarren; Cristiane Flora Villarreal; Patricia Santos de Oliveira; Amado Nizarala de Ávila (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to assess pain management during labor. Methods: a cross-sectional study was carried out by reviewing medical records and conducting postpartum interviews. Prevalence and effectiveness of analgesia were assessed. Results: the prevalence of non-pharmacological analgesia was 61.86% of 215 women in labor in Obstetric Center and 82.51% of 62 in midwife-led unit. Prevalence of severe pain, on the Visual Analogue Scale, before and after non-pharmacological analgesia, was from 92.16% to 64.04% (p=0.00) in Obstetric Center and from 85.96% to 52.63% (p=0.01) in midwife-led unit. Prevalence of pharmacological analgesia in Obstetric Centers was 15.81%, with no variation in severe pain (p=0.57). Patients' request for analgesia was associated with education (p=0.00) and pain intensity (p=0.02). Conclusions: non-pharmacological analgesia improved pain intensity. Prevalence of pharmacological analgesic prescription was lower than that identified in developed countries. Pain management needs to consider the preferences and needs of women in labor.